Biological Functions: A Critical Review and A Proposal - Alarcón, Nicolás (Revista de Humanidades de Valparaíso, 2022)
This research aims to propose a new theory to account for the functions of biological objects. For this, I will show that the most accepted theories of biological functions fail, and then I will propose a new alternative that overcomes the given counterexamples. The research is divided into the following questions: i) appealing to various counterexamples, noting that there is no robust theory capable of accounting for the phenomenon; finally ii) I will give a minimal provisional / operational theory, which allows us to continue incorporating the functional dimension of the features.